Calcium Carbonate Particles Filled Homopolymer Polypropylene at Different Loading Levels: Mechanical Properties Characterization and Materials Failure Analysis - Yucheng Peng (MDPI AG, 2021)
Calcium carbonate (CaCO3) particles have been widely used in filling thermoplastics for different applications in automotive, packaging, and construction. No agreement has been reached in the research community regarding the function of CaCO3 for enhancing toughness of homopolymer polypropylene (HPP). This study was to understand the effect of different loading levels of CaCO3 on HPP toughness, including notched and unnotched impact strength. A batch mixer was used to thermally compound CaCO3 particles with HPP at loading levels of 10, 20, 30, 40, and 50 wt.%, followed by specimen preparation using an injection molding process. The mechanical properties of the composites, including tensile, flexural, and impact were characterized. The results indicated that tensile strengths decreased significantly with increasing loading levels of CaCO3 particles while the tensile and flexural modulus increased significantly with increasing particle loadings. The composite tensile properties changed linearly with increasing CaCO3 loadings. The notched Izod impact strength of the composites was sustained by adding CaCO3 particles up to 40 wt.% while the unnotched impact strength decreased significantly with the addition of CaCO3 particles. Different deformation mechanisms between notched (fracture propagation) and unnotched (fracture initiation and propagation) impact tests were proposed to be the reason.